2012
DOI: 10.1097/sap.0b013e31824671e5
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Fluorescence Imaging of Lymphatic Regeneration in Nonhuman Primate Facial Vascularized Composite Allografts

Abstract: Donor-recipient lymphatic channel regeneration following VCA did not result in resolution of edema. Technical causes of graft edema may be overcome with alternative surgical techniques, allowing for direct investigation of the immunologic relationship between VCA graft edema and rejection responses. Mechanisms and timing of dynamic donor-recipient lymphatic channel relationships can be evaluated using fluorescent imaging systems to better define the immunologic role of lymphatic channels in VCA engraftment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
8
1
Order By: Relevance
“…In addition, our findings vary from the only other study that examined lymphatic drainage in vascularized composite allografts . In this study, NIR lymphography of nonhuman primate heterotopic facial allografts revealed that nonsuperficial cutaneous lymphatic drainage of the graft, as assessed by edema patterns, did not improve until 2 weeks post operation.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…In addition, our findings vary from the only other study that examined lymphatic drainage in vascularized composite allografts . In this study, NIR lymphography of nonhuman primate heterotopic facial allografts revealed that nonsuperficial cutaneous lymphatic drainage of the graft, as assessed by edema patterns, did not improve until 2 weeks post operation.…”
Section: Discussioncontrasting
confidence: 79%
“…In the allogeneic transplant group, visualization of lymphatic channels on POD 5 correlated with both advanced rejection by POD 6 or 7 and significant disruption of lymphatic flow once the limb had progressed to advanced rejection . Our findings indicate that cutaneous lymphatic reconstitution occurs in parallel with the acute inflammatory period after hind limb transplantation.…”
Section: Discussionmentioning
confidence: 56%
“…Studies of lymphatic draining using indocyanine green (ICG), imaging in a nonhuman primate model of face transplantation demonstrated that reduction of facial swelling post‐transplant correlated with superficial donor–recipient lymphatic channel reconstitution . However, the normal rapid flow of dye from the superficial to the deep lymphatic system through multiple small channels did not develop post‐transplantation . Interestingly, rejection episodes did not seem to alter the lymphatic drainage patterns.…”
Section: Tissue Components Of Composite Allograftsmentioning
confidence: 99%
“…Interestingly, rejection episodes did not seem to alter the lymphatic drainage patterns. The authors concluded that VCA graft edema might be overcome by performing lymphaticovenous and or lymphaticolymphatic anastomosis during the transplant procedure . Our center is currently implementing protocols using subcutaneous ICG injection as a method to monitor lymphatic drainage and pilot studies have also suggested a dominance of superficial vs. deep drainage in transplant recipients vs. a normal control.…”
Section: Tissue Components Of Composite Allograftsmentioning
confidence: 99%
“…9,10,1416 Improved lymphatic target identification using 2 modes of lymphatic mapping is well documented in oncologic surgery with both lymphoscintigraphy and ICG imaging.. 17 Furthermore, ICG is more effective than isosulfan blue in sentinel node lymphography, identifying 100% of sentinel lymph nodes identified by lymphoscintigraphy, whereas isosulfan blue identified only 86%. 18,19 When using the dual-dye technique for leak identification, ICG lymphography should be performed first so that the operative field remains visually unobscured.…”
Section: Discussionmentioning
confidence: 99%